Evaluation of Accounting Information Systems Based on Open-ERP At Pharmacy: A Case Study - Ekasari, Kurnia; Mustofa, Ahmad; Kusmintarti, Anik (CV ODIS, 2021)
By using the critical success factors of enterprise resource planning, this study aims to determine the success rate of ERP that has been implemented. This research was a qualitative research to describe the evaluation of the implementation of Enterprise Resource Planning. The object of this research was Tirta Pharmacy located in Jember Regency, East Java. The type of data in this study was primary data in the form of observations and interviews with pharmacists at Tirta Pharmacy. Data analysis was carried out to evaluate the implementation of ERP by using Critical Success Factors (CSF) from the results of a literature review of various sources. This was used as a reference for how effective the implementation was in the Company. The results of this study prove that ERP implementation has succeeded in helping the company's operational activities because there is support from top management, project management, adequate training and education, sharing knowledge, and clear vision and goals that have been determined.